Molecular Recognition of 2,6-Dihydroxybenzoic Acid Polymorph In Ethanol, Methanol and P-Xylene Solution - Fatmawati, Adam; Nurul Kalyisah, Abd Khar (2012)

(untitled)
2,6-dihydroxybenzoic (DHB) acid is an active pharmaceutical ingredient exhibits polymorphism when it is in crystalline form. The selection of appropriate solvent plays a significant role in the formation of the desirable FI and FII polymorph of 2,6- dihydroxybenzoic acid crystal solid. In this extended research study, molecular dynamics was applied to simulate the behavior of 2,6-dihydroxybenzoic acid solute in ethanol, methanol and p-xylene solvents at 20oC using COMPASS force field in Material Studio package. The molecules were labelled as illustrated in Figure 1 to recognize the specific individual atoms which might impart to the significant intermolecular interaction and synthons that lead to the different hydrogen bonding networking in the crystal polymorph. The dynamics run for pure solvent and binary system were equilibrated initially in NVE ensemble at 500 ps and followed by NPT ensemble at 1500 ps to get the desired radial distribution function (rdf) of 2,6-DHB in the solution. At similar ratio number of solvent:solute, the rdf of solute-solute interaction in methanol solution indicates a stronger hydrogen bonding networking and different synthons compared in ethanol and p-xylene solutions which is in agreement that 2,6- DHB has highest solubility in methanol. Experimental study has found that FI form is crystallised from p-xylene meanwhile FII form was crystallised from ethanol and methanol solvents.